Synthesis, Crystal Structure, and Characterization of a Congruent Melting Compound Magnesium Strontium Diborate MgSrB2O51. Issue 8 (25th March 2014) - Guo, Xinfeng; Wu, Hongping; Pan, Shilie; Yang, Zhihua; Yu, Hongwei; Zhang, Bingbing; Han, Jian; Zhang, Fangyuan
Abstract A congruent melting compound MgSrB2O5 was synthesized by high temperature solution method from the MgO‐SrO‐B2O3 system, and the structure was determined by single‐crystal X‐ray diffraction methods. The compound crystallizes in the monoclinic system, with space group P21/c. The crystal structure is composed of isolated B2O5 units and MgO6 octahedra that are connected to form two‐dimensional [Mg2B4O10] layers stacking along the c axis. The layers are bridged by the Sr2+ cations to form a three‐dimensional framework. The IR spectrum and the thermal properties of MgSrB2O5 were also reported. Additionally, detailed structure comparisons between MgSrB2O5 and other borates, such as Mg2B2O5, Sr2B2O5 and SrCdB2O5 are carried out and the first‐principle theoretical studies are performed to aid the understanding of electronic structures and linear optical properties.